(untitled) (Proceedings of International Conference on Special Education, 2023)
Multiplication can pose significant challenges for primary school students, especially those with special educational needs (SEN). These challenges may contribute to Malaysia’s low performance in mathematics, as measured by the Programme for International Student Assessment (PISA). Difficulties with multiplication may lead to anxiety and poor performance in mathematics overall, making it challenging for students to achieve proficiency at higher levels. This study aims to improve SEN students’ performance in multiplication and reduce their anxiety level in mathematics by using the M-Technique. The central research question is whether the M- Technique can improve the multiplication performance and reduce anxiety levels among primary school students with special educational needs in Malaysia. The study employed quantitative methods to collect data on the students’ performance and anxiety levels before and after using the M-Technique, utilizing two learning tools: the "nine-box grid tool" and the "easy column multiplication tool." The study participants were five SEN students from Year 3 at a school in Seremban, Negeri Sembilan. Data collection methods included a questionnaire, pre-post-test, and interview, with two intervention sessions utilizing the M-Technique. The data analysis conducted for this study indicates that the M-Technique significantly enhanced the students’ proficiency in solving multiplication problems up to four digits by one digit without the need for teacher guidance. Specifically, the results revealed a remarkable improvement in the students’ multiplication performance following the intervention, as evidenced by the significant increase in their post-test scores. The findings suggest that the M-Technique can serve as an effective alternative for inclusive students to learn multiplication. Therefore, the study contributes to the development of inclusive teaching methods and may assist in improving Malaysia’s overall mathematics performance.